Seasonal Variations in Blood Pressure and Increased Incidence of Intracerebral Hemorrhage in Cold Months of the Year - Samiullah Khan, Gohar Ali Khan, Naseeb Ur Rehman Shah, Saeed Maqsood, Radhia Khan, Attaullah (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the Seasonal variations in Blood Pressure and increased incidence of Intracerebral Hemorrhage in cold months of the year Methods: This cross sectional study was conducted at KGN hospital, during the time period of one year. The months of the year was divided as cold months (November-February) and all other months (March-October) of the year. Ischemic stroke and intracerebral hemorrhagic stroke were the two main categories used to categorize individuals with stroke based on non contrast brain CT scan along with clinical characteristics. Results: In cold months, the incidence of Intracerebral hemorrhage, 98 (65.3%) was significantly greater at p < 0.05 as compared to all other months of the year, 52 (34.7%). Both systolic and diastolic blood pressure of intracerebral hemorrhage patients was higher in cold months as compared to all other months of the year Conclusion: The good reason for increase in both systolic and diastolic blood pressure of intracerebral hemorrhage patients is the peripheral vasoconstriction of the vessels in cold weather. Keywords: Intracerebral hemorrhage, seasonal variations, Ischemic stroke, cholesterol, blood pressure.